Exposition of Genesis - Leupold, Herbert Carl, 1892-1972 (London, UK Evangelical Press, 1942)
Contents: vol. 1 and 2 of the original work. Includes bibliographical references.
1972 reprint.
Keywords: Bible. O.T. Genesis -- commentaries